Implementasi Pembiasaan Religius dalam Mewujudkan Profil Pelajar Pancasila ‘Beriman, Bertakwa, dan Berakhlak Mulia’ di SDN 1 Purbalingga Lor - Hanun, Rizqy Adinda Fadhilah; Wakhudin, Wakhudin (Universitas Sebelas Maret, 2025)
This study aims to describe the implementation of religious habits in realizing the Pancasila Student Profile in grade III of SDN 1 Purbalingga Lor, obstacles, and their solutions. These habits are important to implement because they are a way to realize the Pancasila Student Profile ‘Faithful, God-fearing, and of Noble Character’. This study uses a qualitative-descriptive approach with a case study method. The research subjects are third-grade students, classroom teachers, and the school principal. Data was collected through observation, interviews, and document analysis. Data was analyzed using the Miles & Huberman model through the steps of data collection, data reduction, data display, and data presentation. The results of the study indicate that the religious habits practiced at SDN 1 Purbalingga Lor are divided into routine and programmed habits. There are obstacles in the implementation of these practices, such as inadequate facilities and students who sometimes find it difficult to follow the practices. However, solutions such as monitoring and maximizing existing potential are always implemented to ensure that the practices can continue to run smoothly. It can be said that the implementation of religious habits can effectively realize the Profile of Pancasila Students who are Faithful, God-fearing, and of Noble Character, as evidenced by the attitudes and behaviors of students in the third grade.Penelitian ini bertujuan untuk mendeskripsikan implementasi pembiasaan religius dalam mewujudkan Profil Pelajar Pancasila di kelas III SDN 1 Purbalingga Lor, hambatan yang dihadapi, dan solusinya. Pembiasaan ini penting dilaksanakan karena ini merupakan cara untuk mewujudkan Profil Pelajar Pancasila Beriman, Bertakwa, dan Berakhlak Mulia. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan metode studi kasus. Subjek penelitian ini adalah peserta didik kelas III, guru kelas, dan kepala sekolah. Data diperoleh dengan observasi, wawancara dan studi dokumentasi. Data dianalisis menggunakan model Miles & Huberman melalui langkah pengumpulan data, reduksi data, displai data, dan penyajian data. Hasil penelitian menunjukkan bahwa, pembiasaan religius yang dilaksanakan di SDN 1 Purbalingga lor dibagi pembiasaan rutin dan terprogram. Terdapat hambatan dalam pelaksanaan pembiasaan berupa fasilitas yang belum memadahi dan dari peserta didik yang kadang sulit mengikuti pembiasaan. Meski demikian, solusi seperti adanya monitoring dan memaksimalkan potensi yang ada selalu dilakukan agar pembiasaan bisa terus berjalan dengan baik. Dapat dikatakan, pelaksanaan pembiasaan religius dapat mewujudkan Profil Pelajar Pancasila Beriman, Bertakwa, dan Berakhlak Mulia dengan baik dapat dilihat dari sikap dan perilaku peserta didik di kelas III.